Why should my department consider offering a violence studies course? - Goodney-Lea, Suzanne (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
First and foremost, this is one of the "sexy" topics, and, much as we doth protest the "nuts, sluts, perverts" variety of sociology, it fills classrooms and pays the bills. At a time when departmental budgets are being deeply slashed, this is no small consideration. Whether we like it or not, the sex and death courses are what our students flock toward. Perhaps Freud was onto something. If we renamed Demography, "Sex and Death", I’d venture to guess that we’d see a higher enrollment there, too. This is not to say that, because a topic might seem lurid, it cannot also provide a forum for conveying substantive concepts. Whatever we might call Demography, we will always explore the same core principles therein. Violence Studies or even The Sociology of Murder is no different. Whatever the subject of our inquiry, the sociological tool kit, i.e. the methods of thinking and concepts we use to understand social phenomena, is remarkably consistent.